Peran Perguruan Tinggi Ekonomi Islam dalam Mempersiapkan Sumberdaya Manusia Syariah - Rini Elvira (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2015)
The more rapid growth and development of islamic financial institutions (especially the islamic banks) have a positive impact on the increasing need for human resources (HR) sharia. To meet the needs of qualified human resources sharia, professional, and in accordance with the needs and expectations of the Islamic finance industry, required the participation of all parties. One of the parties that have a high contribution is Islamic colleges (PTAI) through the Department of Islamic economics. Department of Islamic economics should play an active role in preparing qualified human resources and professional sharia so as to meet the needs and expectations of the Islamic finance industry. In an effort to produce quality graduates and professionals the Department of Islamic economics can contribute by: (1) Open prgram studies, (2) formulate a curriculum that is appropriate to combine courses that provide knowledge professionalism of economics, finance, banking, business, knowledge of sharia ( law & applications) as well as moral values (faith and morals), (3) Provision of funds development, (4) conduct training that is relevant, (5) the development of research and scientific work, (6) provided facilities for adequate learning; matriculation language, library (complete literature), lab mini bank, (7) the teaching staff of competent and qualified, (8) support programs such as; internships, on-job training.